2019
DOI: 10.3390/antiox8100498
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravenous Iron on Oxidative Stress and Mitochondrial Function in Experimental Chronic Kidney Disease

Abstract: Background: Mitochondrial dysfunction is observed in chronic kidney disease (CKD). Iron deficiency anaemia (IDA), a common complication in CKD, is associated with poor clinical outcomes affecting mitochondrial function and exacerbating oxidative stress. Intravenous (iv) iron, that is used to treat anaemia, may lead to acute systemic oxidative stress. This study evaluated the impact of iv iron on mitochondrial function and oxidative stress. Methods: Uraemia was induced surgically in male Sprague-Dawley rats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 80 publications
1
23
1
Order By: Relevance
“…The glutathione system consisting of glutathione reductase, glutathione oxidase and glutathione, maintains the concentration of O 2 • and H 2 O 2 at physiological levels necessary for tissue repair and immune defence [ 3 ]. Therefore, the ratio of oxidised and reduced glutathione indicates the redox state of a cell and may represent a valuable tool for the assessment of oxidative stress and a target for drug-based antioxidant therapies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The glutathione system consisting of glutathione reductase, glutathione oxidase and glutathione, maintains the concentration of O 2 • and H 2 O 2 at physiological levels necessary for tissue repair and immune defence [ 3 ]. Therefore, the ratio of oxidised and reduced glutathione indicates the redox state of a cell and may represent a valuable tool for the assessment of oxidative stress and a target for drug-based antioxidant therapies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nuhu et al [ 37 ] recently examined the mechanistic links between iron and CKD and concluded that the overall oxidation status in CKD is antioxidant. An interplay exists between iron homeostasis and oxidative stress in CKD that in turn impacts the effects of IV iron treatment [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…infusion may cause tissue damage via oxidative stress or increase susceptibility to infection. 31,70,71 Studies have both supported and refuted these concerns, with the balance of evidence suggesting that exposure to i.v. iron does not result in any greater risk of severe adverse reactions compared with oral iron or placebo.…”
Section: Iron Repletion and Adverse Eventsmentioning
confidence: 99%
“…iron does not result in any greater risk of severe adverse reactions compared with oral iron or placebo. 70…”
Section: Iron Repletion and Adverse Eventsmentioning
confidence: 99%